Fiscal Management Practices Framework of State Universities and Colleges in Region XII - Mamburao JR., Ruben S.; Manubag, Edgar B. (International Journal of Scientific Research and Management (IJSRM), 2023)
This study examined the correlation between financial literacy, decision-making practices, internal control systems, and their impact on fiscal management practices in State Universities and Colleges (SUCs) within Region XII using a quantitative descriptive correlational approach. Using Pearson Correlation, the results demonstrated that these three factors are highly prevalent in SUCs and significantly influence their fiscal management practices. Interestingly, the study found that educational attainment does not mediate this relationship, as indicated by the Hayes Macro Process Model.Moreover, the stepwise multiple regression analysis revealed that only internal control systems and financial literacy substantially affected fiscal management practices, highlighting their critical role in shaping these practices. Based on these findings, the study recommends that SUCs prioritize financial education and decision-making training and reinforce internal control systems to enhance fiscal management.By implementing these measures, SUCs can maintain efficient and effective fiscal management practices, thereby supporting their overall institutional success and financial sustainability within the region. The significance of financial literacy, decision-making procedures, and internal control systems in shaping the fiscal management practices of educational institutions is highlighted in this study.